Physiological gender differences associated with sprint skiing performance - Sandbakk, O.; Ettema, G.; Leirdal, S.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Highly trained sprint cross-country skiers are well trained in their upper and lower extremities (Holmberg 2009) and have high aerobic and maximal speed capacities (Sandbakk et al. 2010). Accordingly, sprint skiers may be relevant subjects for evaluating gender differences when employing whole body exercise through a range of physiological capacities. The purpose of the present study was to examine gender differences in performance and physiological characteristics of elite sprint cross-country skiers. Furthermore, we aimed to see whether normalizing for lean body mass would explain these differences between men and women.